Placental fusion in a dichorionic-diamniotic IVF twin pregnancy – case presentation - Andreea CALOMFIRESCU-AVRAMESCU (Romanian Journal of Medical Practice, 2020)
Twin pregnancies have an increased incidence in recent years, especially due to the development of assisted human reproduction techniques. Although most of the in vitro fertilization pregnancies are dichorionic tasks, exceptions may also occur following the placental fusion process. Twin pregnancies in which the fusion process occurs associate the complications of monochorial pregnancies such as prematurity, growth discordance between the twins, twin-to-twin transfusion syndrome, twin reversed arterial perfusion, with higher perinatal mortality and morbidity. In recent years, most studies have focused on correlations between the macro and microscopic aspects of the placenta and the associated complications.